Soil Studies in Andaman Evergreen forests - Yadav, J. S. P. (Indian Forester, 1967)
The paper describes a soil study undertaken in the tropical evergreen forests of Andaman Islands in 1960. Owing to intensive leaching caused by heavy rainfall the soils are acidic, non-calcareous and have low calcium status excepting those soils which are either poorly drained or are located at the low-lying sites. In general, the soils possess fairly good amount of clay fraction and show high water holding power and cation exchange capacity, but the organic matter content is some what low especially at the hill tops as a result of rapid rate of its decomposition obtaning under the local conditions. The availability of phosphorus is low, but there is greater mobilisation of manganese in the water-logged soil. The soils along the water courses associated with subsoil swampy condition and also the red earths having compact concretionary mass do not appear to be favourable for the natural regeneration of certain Dipterocarpus species. Great care is required to carry out heavy working in these forests, since it may accentuate water-logging in the low-lying sites and increase the risk of erosion on the higher hill slopes.